Peningkatan Prestasi Belajar Biologi Melalui Pemberdayaan Penalaran Siswa - Jailani Jailani (Universitas Syiah Kuala, 2009)
One of the main goal of science education is to support students’ intellegency development. Therefore, in this term, the goal is most of students could be function at logic thinking level. Generally for science learning, logic thinking does not manage directly, planned and intentionally. The lack of students in problem solving and think logically has influenced students’ achievement. Lower level of students’ thinking process was one of problem resources. Preparation of qulified students could be conducted through problem solving, such as thinking improvement approach, strategy, or method, also any learning technique